THE ROLE OF STYLISTIC DEVICES IN SHAPING TONE AND MEANING IN MODERN ENGLISH PROSE - Ma’rufova Diyorakhon; G’ofurova S. M. (TADQIQOTLAR, 2026)
Abstract. This article examines the role of stylistic devices in shaping tone and meaning in modern English prose. It explores how linguistic and literary techniques such as metaphor, irony, symbolism, and alliteration contribute to the expressive power of texts. The study highlights the ways in which authors use stylistic devices to influence readers’ perception, evoke emotions, and construct deeper layers of meaning. Special attention is given to the pedagogical importance of stylistic analysis in understanding literary works and improving language competence.